2010
DOI: 10.2169/internalmedicine.49.3789
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis Associated with Epstein-Barr Virus Infection

Abstract: Infectious mononucleosis is a self-limiting clinical syndrome caused by primary Epstein-Barr virus (EBV) infection. EBV-associated gastritis, however, has rarely been documented. We report a case of a 17-year-old woman who presented with fever, sore throat, and epigastric pain. Upper endoscopy revealed diffuse granular mucosae and elevated lesions in the stomach. Histologically, the biopsied mucosa was infiltrated by numerous atypical lymphocytes. From clinical, histopathologic, immunohistochemical, and in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…However, in the present case, atypical large B cells or CD30-positive ReedSternberg-like cells and other types of immunoblastic cells were not found in ulcerative lesion, suggesting a pathogenesis distinct from that of EBVMCU underlies the perforated ulcer formation in the ileum. Similar to the present case, although the number of the reports is small, cases with EBVassociated gastro-enteritis forming multiple ulcers without the features of LPD have been reported both in immunocompetent and immunoincompetent adults (10)(11)(12)(13)(14)(15). It is not clear how EBV infection causes ulcer formation in the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, in the present case, atypical large B cells or CD30-positive ReedSternberg-like cells and other types of immunoblastic cells were not found in ulcerative lesion, suggesting a pathogenesis distinct from that of EBVMCU underlies the perforated ulcer formation in the ileum. Similar to the present case, although the number of the reports is small, cases with EBVassociated gastro-enteritis forming multiple ulcers without the features of LPD have been reported both in immunocompetent and immunoincompetent adults (10)(11)(12)(13)(14)(15). It is not clear how EBV infection causes ulcer formation in the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 53%
“…We may not preclude the possibility that immunosupression by MTX treatment caused a delay in antibody production. Of interest, almost all of the reported cases of EBV-associated ulcerative gastritis occurred during primary EBV infection (10)(11)(12)(13)(14). An indication for understanding the mechanism for the correlation of IM and ulcerative gastritis is currently not available.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The second center reported that 4 of 50 patients developed elevated EBV-DNA in the blood, one of whom was found to have EBV gastritis. [20, 25] While the data are limited, interpretation of EBV-DNA copy number in the blood after alloBMT with PTCy remains uncharted territory.…”
Section: Discussionmentioning
confidence: 99%
“…We found only 6 case reports of EBV gastritis in the literature (Table 1)145678). Here we presented a case of EBV gastritis in a previously well 4-year-old girl.…”
Section: Discussionmentioning
confidence: 81%